Reinterpreting Financial Responsibilities in Islamic Marriage: A Maqasid al-Usrah Perspective - Nur Fadhilah; Muhammad Nurravi Alamsyah (Al-Syakhsiyyah: Journal of Law and Family Studies, 2025)
The research aims to address the shift from a rigid, gender-based financial framework to a more equitable model that reflects contemporary socio-economic realities. A qualitative research methodology was employed, analyzing classical and contemporary Islamic legal texts, court rulings, and scholarly debates. The findings reveal a growing consensus among Islamic scholars that qiwamah is not necessarily an exclusive male financial obligation but rather as a shared responsibility between spouses. The study highlights the increasing acceptance of women's financial contributions and the necessity for legal reforms to formalize this shift. Additionally, the mubadalah principle underscores the importance of reciprocity in marital financial duties, ensuring justice and mutual support within family structures. These findings suggest that contemporary Islamic jurisprudence is evolving to accommodate socio-economic changes, fostering a balanced partnership in financial obligations. The implications of this research extend beyond academic discourse and have practical relevance for family law and policy-making. By integrating Maqasid al-Usrah into legal frameworks, policymakers can develop more inclusive laws that reflect gender equity and economic realities. Further research is encouraged to explore how shared financial responsibility affects marital stability and children's well-being in Muslim-majority contexts.